Myofunctional Therapy to Treat Obstructive Sleep Apnea: A Systematic Review and Meta-analysis. Issue 5 (1st May 2015) - Camacho, Macario; Certal, Victor; Abdullatif, Jose; Zaghi, Soroush; Ruoff, Chad M.; Capasso, Robson; Kushida, Clete A.
Abstract: Objective: To systematically review the literature for articles evaluating myofunctional therapy (MT) as treatment for obstructive sleep apnea (OSA) in children and adults and to perform a meta-analysis on the polysomnographic, snoring, and sleepiness data. Data Sources: Web of Science, Scopus, MEDLINE, and The Cochrane Library. Review Methods: The searches were performed through June 18, 2014. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement was followed. Results: Nine adult studies (120 patients) reported polysomnography, snoring, and/or sleepiness outcomes. The pre- and post-MT apneahypopnea indices (AHI) decreased from a mean ± standard deviation (M ± SD) of 24.5 ± 14.3/h to 12.3 ± 11.8/h, mean difference (MD) −14.26 [95% confidence interval (CI) −20.98, −7.54], P < 0.0001. Lowest oxygen saturations improved from 83.9 ± 6.0% to 86.6 ± 7.3%, MD 4.19 (95% CI 1.85, 6.54), P = 0.0005. Polysomnography snoring decreased from 14.05 ± 4.89% to 3.87 ± 4.12% of total sleep time, P < 0.001, and snoring decreased in all three studies reporting subjective outcomes. Epworth Sleepiness Scale decreased from 14.8 ± 3.5 to 8.2 ± 4.1. Two pediatric studies (25 patients) reported outcomes. In the first study of 14 children, the AHI decreased from 4.87 ± 3.0/h to 1.84 ± 3.2/h, P = 0.004. The second study evaluated children who were cured of OSA after adenotonsillectomy and palatal expansion, and found that 11 patients who continued MT remained cured (AHI 0.5 ± 0.4/h), whereas 13 controls had recurrent OSA (AHI 5.3 ± 1.5/h) after 4 y. Conclusion: Current literature demonstrates that myofunctional therapy decreases apnea-hypopnea index by approximately 50% in adults and 62% in children. Lowest oxygen saturations, snoring, and sleepiness outcomes improve in adults. Myofunctional therapy could serve as an adjunct to other obstructive sleep apnea treatments.